2008
DOI: 10.1093/jxb/ern184
|View full text |Cite
|
Sign up to set email alerts
|

Potato skin proteome is enriched with plant defence components

Abstract: Periderm is a tissue of secondary origin that replaces damaged epidermis. It can be found in underground plant organs, as an above-ground tissue of woody species (cork), and as a wound-healing tissue. Its outer layers are composed of phellem cells with suberized walls that constitute a protective barrier, preventing pathogen invasion and fluid loss. In potato, a model for periderm studies, periderm tissue replaces the epidermis early in tuber development and the suberized phellems constitute the tuber's skin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…What is more, at harvesting, potato periderm is highly exposed to dehydration, since in new potatoes, tubers with the periderm not yet mature pass from soil to atmosphere. In agreement with the results hereby presented, a proteomic approach of native periderm showed that 63% of the skin proteins identified were related to stress responses (Barel and Ginzberg 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…What is more, at harvesting, potato periderm is highly exposed to dehydration, since in new potatoes, tubers with the periderm not yet mature pass from soil to atmosphere. In agreement with the results hereby presented, a proteomic approach of native periderm showed that 63% of the skin proteins identified were related to stress responses (Barel and Ginzberg 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the suberization-associated anionic peroxidase, long been proposed in the oxidative crosslinking of suberin aromatics (Bernards et al 1999), is also present in the library. Accordingly, this peroxidase is present in both native and wounded potato periderm proteomes (Barel and Ginzberg 2008;Chaves et al 2009) and Kloosterman et al 2008). a Factor loadings of the six developmental stages for the two PCA axes.…”
Section: Candidate Genes For Suberin and Associated Waxmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that insulation against environmental factors provided by holm oak outer bark could be less efficient than in cork oak. Thus, the significant enrichment in abiotic stress transcripts may also be due to a greater exposure of holm oak outer bark to the environment, as was also described for potato tuber periderm (Barel and Ginzberg 2008;Soler et al 2011). Similarly, the overrepresentation in holm oak external bark of GO terms related to chromatin and translation could be linked to cell damage caused by abiotic stresses such as UV radiation and the need to maintain cellular homeostasis and ensure correct gene regulation (Teixeira et al 2014).…”
Section: Discussionmentioning
confidence: 82%
“…In that work, a list of candidate genes isolated from cork tissues were identified including genes for the synthesis, transport, and polymerization of suberin monomers as well as a number of regulatory genes including members of the NO APICAL MERISTEM (NAM), MYB and WRKY transcription factor families with putative functions in meristem identity and cork differentiation. Since then, a number of studies have been published characterizing the role of a few selected candidate orthologues in potato tuber suberin formation by reverse genetics approaches (Serra et al 2010a;Serra et al 2010b;Serra et al 2009a;Serra et al 2009b) and identifying additional candidates in potato tuber periderm (Barel and Ginzberg 2008;Chaves et al 2009;Ginzberg et al 2009;Soler et al 2011). Despite the remarkable ability of cork oak to produce cork, potato has been the preferred model to study these processes since it is more amenable to in vitro manipulation and transformation having, in addition, its genome fully sequenced (Xu et al 2011).…”
Section: Introductionmentioning
confidence: 99%